تأثير المضادات الحيوية ومتبقياتهاعلى صحه وسلامه الانسان - التميمي, محمد (My University, 2019)
The unpleasant truth is that our use and misuse of antibiotics has eroded their efficiency and fueled the spread of antibiotic resistance
Keywords: Antibiotics,food,human health